Prospects for Innovative Development of International Trade Cooperation for the Population Economic Security - V. A. Puchkov (Учёт. Анализ. Аудит)
The paper reveals the analysis of modern trends of increasing global risks, the preservation of dangers and threats of natural, man-made and bio-social disasters, the emergence of new challenges on a global scale that can lead to global crisis situations. The methodological base of the study includes theories of constructing a new system of economic interstate humanitarian interaction. In this case, there have been applied analysis methods and synthesis, analogies, observations and expert assessments. The study considered the experience of creating institutional joint companies in public security at the international level. There was formed a mechanism as well as methodological recommendations have been prepared for innovative development in the field of crisis management and implementation of the framework program for disaster risk reduction. The analysis of the stages of building an international humanitarian response system with different countries is carried out. The directions of innovative development of international cooperation for the purpose of economic security of the population are proposed. The study of the experience of creating institutional joint organizations allowed to propose an economic model that meets the principles and spirit of international law. The developed recommendations will provide the Russian Federation with an innovative and technological breakthrough in the international humanitarian sphere. The results of the research can be used by public authorities in the formation and implementation of national international policiy for the development of humanitarian bilateral and multilateral cooperation in the field of humanitarian projects, economic security of the population and the prevention of disasters and crises.